Antecedents of responsible environmental behaviour and influence of intention on marine park destination choice among millennial tourists in Malaysia - Abdullah, Siti Intan Nurdiana Wong (2020)
Due to the rising global concern over environmental pollution, ecotourism in protected areas such as marine park islands has been identified as one of the mitigation strategies. Besides promoting sustainable tourism, ecotourism is a key contributor to the country’s economy. However, over the years, there has been a continuous increase in the numbers of visitors to these marine park islands, alongside the growing tourist activities and the irresponsible behaviours of the visitors that threatens the marine ecosystem. Hence, in keeping up with the environmental pressures and the demand for ecotourism activities, many have turned their attention to the millennial generation. Millennial tourists are growing due to their exponential population size, spending power and distinctive characteristics. Despite the numerous efforts that have been made to gain an in- depth understanding of millennial tourists’ behaviours, there is still limited knowledge on the underlying factors that drive their environmental behaviours especially in marine park islands and how this would lead to their holiday destination decisions. This study applied an extended Model of Responsible Environmental Behaviour (REB) with the inclusion of Consumption Values Theory (CVT) and Tripartite Model of Destination Image (TDI). The objective of this study is to examine the antecedents of responsible environmental behaviour of millennial tourists and to determine the effect of behaviour intention in predicting millennial tourists’ pro-environmental behaviours and their destination choice. The antecedents of environmental knowledge and consumption values were formatively constructed and tested empirically with attitude and destination image in the extended framework. Additionally, overall affective and cognitive destination image were applied to predict the conative effect towards responsible environmental behaviour and destination choice among the millennials. Using purposive sampling to represent the local and international millennial tourists accordingly, a total of 427 data were analysed from tourists who had recently visited a marine park island in Malaysia. The face-to-face survey was conducted at six jetties located in Malaysia, at exit points of the marine park islands. After the data collected was screened and analysed using descriptive statistics, the reliability and validity of the measurement model were determined using Partial Least Square-Structural Equation Modelling (PLS-SEM). Results revealed that consumption values were the main predictor of behaviour intention followed by environmental knowledge and attitude. This indicates that millennial tourists’ behaviour intention is highly value-driven, rather than just a rational or altruistic decision as anticipated in earlier theories. Additionally, responsible environmental behaviour was empirically proven to have a more significant effect on destination decision compared to the destination image. The role of intention as a mediator was also strengthened in this study. However, one of the limitations of this study is it only focuses on marine parks. Due to the environmental issues that are constantly evolving and more critical, predicting tourist behaviours is increasingly complex which may render more variables to be included in the study. Other methodological limitations and data collection constraints were addressed. Overall, this study was able to empirically support the extended REB framework to effectively explain and predict responsible environmental behaviour and destination choice among millennial tourists. It also contributed to the body of knowledge on millennial tourists that could assist marketing and ecotourism practitioners in attracting the right market segment towards sustainable tourism development of marine park islands in Malaysia. Based on the results, it is suggested that millennial tourists’ consumption values can be heightened if practitioners develop unique eco-tour programs and promote eco-friendly practices using targeted marketing communications. Millennial tourists who are more engaged in responsible environmental behaviours would display higher tendencies in choosing marine park islands as their next holiday destination. In terms of policy contributions, courses in environmental management can be offered to increase the knowledge of millennials and upgrade their skills on relevant strategies to protect the natural environment. Besides, marine parks’ destination image can be enhanced by highlighting the underwater marine life to promote responsible behaviours in the marine park islands effectively.